2000
DOI: 10.1029/1999gl002338
|View full text |Cite
|
Sign up to set email alerts
|

Shallow throughflow variability in the outflow Straits of Indonesia

Abstract: Abstract. Since December 1995, the Indonesian throughflow has been monitored in five major passages as it flows from the Indonesian interior seas to the Indian Ocean. Pressure differences across the straits enable us to infer the geostrophic surface flow, and so provide the first simultaneous time-series measurements of surface geostrophic flow through these passages. Intraseasonal signals (30-90 day) are a ubiquitous feature in the surface flow, and are consistent with wind-forced Kelvin waves from both the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 18 publications
5
54
1
Order By: Relevance
“…An earlier version with only one third the horizontal mixing strength had a transport of 185 Sv, consistent with other GCMs with weaker horizontal mixing such as 180 Sv (FRAM ¤ 1991) and 190 Sv (Semtner and Chervin 1988). Our modelled transport through the Indonesian Archipelago of 17 Sv with both the BS and CA open (Table 1) is also higher than observational estimates of 7-15 Sv (Meyers et al 1995;Chong et al 2000) but comparible with those found in other modelling studies (e.g. 15-18 Sv, Semtner and Chervin (1988); 15 Sv, Gwilliam (1995)).…”
Section: Model Resultscontrasting
confidence: 33%
See 1 more Smart Citation
“…An earlier version with only one third the horizontal mixing strength had a transport of 185 Sv, consistent with other GCMs with weaker horizontal mixing such as 180 Sv (FRAM ¤ 1991) and 190 Sv (Semtner and Chervin 1988). Our modelled transport through the Indonesian Archipelago of 17 Sv with both the BS and CA open (Table 1) is also higher than observational estimates of 7-15 Sv (Meyers et al 1995;Chong et al 2000) but comparible with those found in other modelling studies (e.g. 15-18 Sv, Semtner and Chervin (1988); 15 Sv, Gwilliam (1995)).…”
Section: Model Resultscontrasting
confidence: 33%
“…The OGCM was initialized with climatological temperature (Levitus et al 1994) and salinity (Levitus and Boyer 1994) Gordon (1986); Schmitz (1995) b Nowlin and Klinck (1986); Grose et al (1995) c Meyers et al (1995); Chong et al (2000) less than 250 m, consistent with the 150 m depth used by Goosse et al (1997a). Each integration was for 4500 years.…”
Section: Model Resultsmentioning
confidence: 99%
“…The different branches of this broad throughflow have velocities of 10s of centimeters per second up to 1 m s −1 or more in the main Indonesian straits such as the Makassar, Lombok, or Ombai Straits (e.g. Chong et al 2000, Sprintall et al 2009). As adult leatherbacks travel at a typical swimming speed of 0.4 to 0.6 m s −1 (Eckert 2006, Fossette et al 2010a, individuals attempting to return to their natal beach would often be slowed, stopped, or even moved backwards by the currents, making the trip particularly challenging.…”
Section: Missing Dispersal Patternsmentioning
confidence: 99%
“…The potential predictability of ocean dynamics in the proximity of the ITF has attracted considerable interest in recent years [Qiu et al, 1999;Chong et al, 2000;Potemra et al, 2002;Syamsudin et al, 2004;Wijffels and Meyers, 2004;Iskandar et al, 2005Iskandar et al, , 2006Yu and Potemra, 2006;Atmadipoera et al, 2009]. For example, Wijffels and Meyers [2004] explored observation-based temperature and sea level variability within the Indonesian seas and southeast Indian Ocean.…”
Section: Introductionmentioning
confidence: 99%